IMPLEMENTASI TEORI BELAJAR KOGNITIF MELALUI MEDIA PAPAN MUSI PADA PEMBELAJARAN KPK DI SD - RAHMA AYUNI; RYAN DWI PUSPITA (Jurnal Pendidikan Dasar, 2025)
This study aims to analyze the application of cognitive learning theory through the media of Musi Board (Multifunctional Board) in improving the conceptual understanding of 5 Grade elementary school students in the Smallest Common Multiples (KPK). The research background is based on the global challenges in building students’ mathematical conceptual thinking skills, which is exacerbated by the dominance of procedural methods. A descriptive qualitative approach was used to observe the process of constructing students’ knowledge through interaction with the media of the Musi Board. Data were collected through passive participant observation and description diagnostic tests. The results of the study show that the Musi Board acts as an effective cognitive scaffolding, bridging students’ concrete and abstract thinking through sensorimotor and manipulative experiences. Physical interaction with the media facilitates the visualization of patterns and relationships between numbers, forming an accurate mental representation of the concept of the KPK. In addition, these implementations create a dynamic and participatory learning environment, where group discussions deepen students’ conceptual understanding and hone their metacognitive skills. In conclusion, the integration of cognitive learning theory with Musi Board media has proven to be effective in improving the quality of mathematics learning in elementary schools, shifting students’ understanding from procedural memorization to deep conceptual understanding.